ANtiangiogenic Second-line Lung cancer Meta-Analysis on individual patient data in non-small cell lung cancer: ANSELMA. (May 2022) - Remon, Jordi; Lacas, Benjamin; Herbst, Roy; Reck, Martin; Garon, Edward B.; Scagliotti, Giorgio V.; Ramlau, Rodryg; Hanna, Nasser; Vansteenkiste, Johan; Yoh, Kiyotaka; Groen, Harry J.M.; Heymach, John V.; et al.
Abstract: Background: Now that immunotherapy plus chemotherapy (CT) is one standard option in first-line treatment of advanced non-small cell lung cancer (NSCLC), there exists a medical need to assess the efficacy of second-line treatments (2LT) with antiangiogenics (AA). We performed an individual patient data meta-analysis to validate the efficacy of these combinations as 2LT. Methods: Randomised trials of AA plus standard 2LT compared to 2LT alone that ended accrual before 2015 were eligible. Fixed-effect models were used to compute pooled hazard ratios (HRs) for overall survival (OS, main end-point), progression-free survival (PFS) and subgroup analyses. Results: Sixteen trials were available (8, 629 patients, 64% adenocarcinoma). AA significantly prolonged OS (HR = 0.93 [95% confidence interval CI: 0.89; 0.98], p = 0.005) and PFS (0.80 [0.77; 0.84], p < 0.0001) compared with 2LT alone. Absolute 1-year OS and PFS benefit for AA were +1.8% [−0.4; +4.0] and +3.5% [+1.9; +5.1], respectively. The OS benefit of AA was higher in younger patients (HR = 0.87 [95% CI: 0.76; 1.00], 0.89 [0.81; 0.97], 0.94 [0.87; 1.02] and 1, 04 [0.93; 1.17] for patients <50, 50–59, 60–69 and ≥ 70 years old, respectively; trend test: p = 0.02) and in patients who started AA within 9 months after starting the first-line therapy (0.88 [0.82; 0.99]) than in patients who started AA later (0.99 [0.91; 1.08]) (interaction: p = 0.03). Results were similar for PFS. AA increased the risk of hypertension (p < 0.0001), but not the risk of pulmonary thromboembolic events (p = 0.21). Conclusions: In the 2LT of advanced NSCLC, adding AA significantly prolongs OS and PFS, but the benefit is clinically limited, mainly observed in younger patients and after shorter time since the start of first-line therapy. Highlights: The addition of antiangiogenics (AA) in second line reduces 20% the risk of progression. The addition of AA in second line reduces 7% the risk of death. The benefit is higher in younger patients and in those with platinum-refractory tumours. However, addition of AA significantly increased the risk of grade ≥3 toxicities.